Effect of Polypropylene and Basalt Fiber on the Behavior of Mortars for Repair Applications. (17th July 2016) - Jiang, Chaohua; Huang, Shanshan; Zhu, Yuwen; Lin, Yifeng; Chen, Da
Abstract : The fresh, mechanical, and durability properties of the polypropylene fiber-reinforced mortar (PP FRM) and the basalt fiber-reinforced mortar (BFRM) with various fiber contents were tested in this paper. The test results show that the presence of polypropylene (PP) fiber and basalt fiber (BF) in the mortar reduces the initial slump flow and increases the slump flow loss rate. The bond strength and flexural strength of fiber-reinforced mortar (FRM) are improved, whereas no obvious improvement on the compressive strength has been observed. Compared with the control mortar, the bond strength of PP FRM and BFRM reinforced with 0.6 kg/m 3, 1.6 kg/m 3, and 2.6 kg/m 3 fiber increases by 16.60%–28.80% and 10.60%–21.40%, respectively. Furthermore, FRM shows lower drying shrinkage, superior abrasion resistance, water impermeability, and freeze-thaw resistance compared with the control mortar. The abrasion resistance strength of PP FRM and BFRM is 77.30% and 38.65% more than the control mortar with 2.6 kg/m 3 fiber content. Therefore, PP FRM and BFRM are suitable to be utilized as repair materials, especially in repairing hydraulic structures surfaces with excellent bond strength and abrasion resistance.